2020
DOI: 10.1021/acs.chemrestox.9b00370
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes Modulate Activity of Cytotoxic Compounds via a Trojan Horse Mechanism

Abstract: Carbon nanotubes (CNTs) are an emerging drug delivery system, but their success is thwarted by potential toxicity concerns. In vitro and in vivo studies imply toxic potential of CNTs, but their potential to influence toxicity of coadministered compounds still remains elusive. Therefore, the present study was conducted to determine the effect of multiwalled CNTs (MWCNTs) on the toxicity of cytotoxic compounds in macrophage (RAW 264.7), lung epithelial (A549), and breast cancer (MCF-7) cell lines. The results su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Ltd., India. The size characteristics were confirmed by high resolution transmission electron microscopy, and impurities were quantified by thermogravimetry; the characterization of these CNPs is described in earlier reports from our group. , …”
Section: Methodsmentioning
confidence: 70%
See 3 more Smart Citations
“…Ltd., India. The size characteristics were confirmed by high resolution transmission electron microscopy, and impurities were quantified by thermogravimetry; the characterization of these CNPs is described in earlier reports from our group. , …”
Section: Methodsmentioning
confidence: 70%
“…A stock solution of CNPs was prepared in water or deuterated water by probe sonication as described earlier. , Briefly, 10 mg of CNP powder was added into an aqueous solution of 10 mg/mL of Tween-80 (prepared in water or deuterated water) and sonicated for 5 min. The stock suspension was appropriately diluted with 10 mg/mL of Tween-80 solution (prepared in water or deuterated water) to obtain the desired concentrations of CNPs, and spectra were recorded within 1 h of sample preparation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At studying the effect of MWCNTs on the toxicity of cytotoxic compounds in macrophage (RAW 264.7), lung epithelial (A549), and breast cancer (MCF-7) cell lines, it was found that hydrophilicity/lipophilicity of the compounds was determinant. The dependence of log P vs. cytotoxic activity showed a quasi-parabolic course, the highest value being observed at log P close to 1 and the degree of cellular uptake of MWCNTs affected the cytotoxicity of drug/MWCNT combinations, suggesting that MWCNTs function as a "Trojan horse", ensuring improved intracellular delivery of drugs leading to increased cytotoxic activity [274]. Nahle et al [275] compared in vitro responses of rat alveolar NR8383 cells to pristine, anionic, and cationic MWCNTs using cytotoxicity assays, transcriptomics, and proteomics.…”
Section: Multi-walled Carbon Nanotubesmentioning
confidence: 99%